Production of photosensitive structures based on CdSe nanoparticles and carbon nanotubes by physical methods - Oday A.H. Hassoon; Odai N.S. Salman; Vladislav N. Mironyuk; Mikhail V. Pozharov; Tatiana Ya. Karatyshova; Andrey M. Zacharevich; Evgeny G. Glukhovskoy (Modern Electronic Materials)
The paper shows the possibility of producing photosensitive structures using physical methods without the use of chemical synthesis and vacuum techniques. Suspensions of CdSe nanoparticles were produced by pulsed laser ablation in a liquid medium (chloroform), and layers of semiconductor material (CdSe) and conductive layers (carbon nanotubes) were formed at the gas-liquid interface and transferred to solid substrates by the Langmuir–Schaeffer method. The size of CdSe nanoparticles in the layers ranged from 60 nm to 200 nm, and the bandgap was 2.3 eV. Multilayer film structures consisting of a layer based on synthesized CdSe nanoparticles and a layer of conductive carbon nanotubes, that demonstrated photosensitivity in the optical region, were obtained. The value of current density under lighting at 1 V and –1 V equals 1.25 mA/cm2 and –1.35 mA/cm2, respectively. The maximum ratio of the illumination current density to the dark current value was 13.5 times (at a voltage of 1 V).